Open Spaces in Low-Rise Residential Units in India: Urban vs Rural - Manoj Panwar; Riya Paulast (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
pen spaces are vital in the spatial, climatic, and socio-cultural fabric of residential architecture. While vernacular rural homes integrate open spaces as multifunctional, climate-responsive elements, urban low-rise residences often treat them as regulatory obligations. Byelaws-driven setbacks have led to a significant gap in understanding how spatial configurations affect microclimate, ventilation, lighting, neighborhood interactions, and openings. This study undertakes a comparative, cross-regional analysis of open spaces in low-rise residential units across urban and rural India, integrating literature review, case studies, spatial composition mapping, and referring to building byelaws and codes. Findings reveal that rural, human-driven open spaces – particularly central courtyards and organically placed courtyards – outperform urban setback-based configurations in terms of microclimate regulations (up to 3 °C lower temperature and better daylight penetration), cross ventilation, and multifunctionality. Though compliant with building byelaws, urban setbacks often result in fragmented, underutilized, and climatically inefficient open spaces. Study recommends that the learnings from regional vernacular architecture be incorporated in urban building byelaws.